(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2026)
Customer relationship management has become an essential tool for strategy for organizations to enhance customer satisfaction and attain a sustainable competitive edge. Effective CRM techniques allow organizations to get a better grasp of customer needs, customize services, build stronger customer relationships and improve service quality. In this study the effect of different CRM strategies on customer satisfaction has been studied. This study considers eight CRM characteristics, namely customer service quality, customization, customer communication, technology-based CRM, customer retention programs, employee competency and trust and relationship development. Around 300 participants answered a structured questionnaire with a 5 point Likert scale as part of the quantitative research approach used to gather the data. The data gathered using SPSS software was subjected to reliability analysis, descriptive statistics, multiple regression analysis, and correlation analysis. The study investigates that in order to improve customer experiences and long-term customer relationship, businesses should concentrate on implementing CRM comprehensively.